2006
DOI: 10.1007/s00330-006-0446-4
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the ankle at 3 Tesla and 1.5 Tesla: protocol optimization and application to cartilage, ligament and tendon pathology in cadaver specimens

Abstract: The objective of this study was to optimize ankle joint MR imaging in volunteers at 1.5 Tesla (T) and 3.0 T, and to compare these optimized sequences concerning image quality and performance in assessing cartilage, ligament and tendon pathology in fresh human cadaver specimens. Initially our clinical ankle protocol consisting of T1-weighted (-w), fat-saturated (fs) T2-w, and short tau inversion-recovery fast spinecho (FSE) sequences was optimized at 1.5 T and 3.0 T by two radiologists. For dedicated cartilage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 31 publications
1
54
1
1
Order By: Relevance
“…In the literature, the accuracy in the detection of cartilage lesions of the knee has been reported to be as high as 87% at 1.5 T and 90% at 3.0 T [21]. For MR imaging of the ankle, sensitivity in detection of cartilage lesions varied between 50% at 1.5 T and 75% at 3.0 T [5,6]. A slightly higher sensitivity was found for MR arthrography (MRA) and computed tomography arthrography (CTA) [22].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In the literature, the accuracy in the detection of cartilage lesions of the knee has been reported to be as high as 87% at 1.5 T and 90% at 3.0 T [21]. For MR imaging of the ankle, sensitivity in detection of cartilage lesions varied between 50% at 1.5 T and 75% at 3.0 T [5,6]. A slightly higher sensitivity was found for MR arthrography (MRA) and computed tomography arthrography (CTA) [22].…”
Section: Discussionmentioning
confidence: 95%
“…Best results were obtained for coronal T1-w MR images with a driven equilibrium pulse. Barr et al reported, that compared to 1.5 T, 3.0 T significantly improved image quality and diagnostic performance in assessing ankle cartilage pathology [6]. IMfs or T2-w fs sequences have been reported to show the best diagnostic performance in the assessment of ankle cartilage [6,24].…”
Section: With Tractionmentioning
confidence: 98%
See 1 more Smart Citation
“…The distinction between acute and chronic osteochondral lesions is difficult using X-ray and is often only possible taking into account the mechanism and time of the incident. An MRI is indispensable for more extensive diagnosis [9,10].…”
Section: Projection Radiographymentioning
confidence: 99%
“…Due the small thickness of the cartilage layer, partial volume effects, particularly in the edge region, are possible. According to studies, the sensitivity of the cartilage lesion image varies from 50 % at 1.5 Tesla and 75 % at 3 Tesla field strength [10]; improvements in diagnostic power can be expected as the technology is developed further. In the clinical setting of most institutions, a routine ankle protocol is used that requires high-resolution sequences suitable for the assessment of articular cartilage.…”
Section: Magnetic Resonance Imaging and Sequence Protocolmentioning
confidence: 99%